2007
DOI: 10.1007/s10571-007-9216-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Processing of Nociception in Cortical Network in Conscious Rats: A Laser-evoked Field Potential Study

Abstract: (1) Field potential study in conscious rats provides a convenient and effective animal model for pain mechanism and pharmacological research. However, the spatial-temporal character of nociception processing in cortex revealed by field potential technique in conscious rats remains unclear. (2) In the present study, multi-channel field potentials evoked by noxious laser stimulation applied to the hind paw of conscious rats were recorded through 12 chronically implanted skull electrodes. Independent component an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 52 publications
3
23
1
Order By: Relevance
“…The analgesic effect of Morphine is thought to origin from both spinal and supraspinal mechanisms. The present study shows that LCEP is depressed by systemic Morphine and thus confirms previous data [15], [18], [43]. However, since Morphine also exhibit sedative properties [44]–[45], the possibility that the entire effect on LCEP is due to its sedative properties could not be excluded.…”
Section: Discussionsupporting
confidence: 91%
“…The analgesic effect of Morphine is thought to origin from both spinal and supraspinal mechanisms. The present study shows that LCEP is depressed by systemic Morphine and thus confirms previous data [15], [18], [43]. However, since Morphine also exhibit sedative properties [44]–[45], the possibility that the entire effect on LCEP is due to its sedative properties could not be excluded.…”
Section: Discussionsupporting
confidence: 91%
“…In the first 60 min (phases 1 and 2) of formalin test, the amount of information flow significantly increased from medial to lateral pathway, whereas it decreased from lateral to medial pathway. Subsequent findings by independent component analysis (ICA) of multichannel field potentials in rats [37] and functional connectivity analysis of human fMRI data [38] confirm the hypothesis that a network of brain regions participates in the nociceptive or tactile processing in a functional connective mode.…”
Section: Descending Modulation Of Sensory Transmissionmentioning
confidence: 64%
“…Similarly, in a laser-evoked field potential study in rats, we observed that nociceptive evoked potentials could be separated into several independent components, which represented the activities of anterior and posterior parietal area, medial frontal area, and anterior cingulate cortex, respectively [36]. Partial directed coherence (PDC) and cross-correlation analysis showed that the direction and amount of information flow between cortical areas presented stable and periodical changes after brief noxious laser stimulation.…”
Section: Modulation Of Central Dynamic Activity By Acupuncturementioning
confidence: 75%
“…Partial directed coherence (PDC) and cross-correlation analysis showed that the direction and amount of information flow between cortical areas presented stable and periodical changes after brief noxious laser stimulation. This suggested that transient noxious stimulation may lead to repeated reciprocal flowing of nociceptive related information within the central neural network [36].…”
Section: Modulation Of Central Dynamic Activity By Acupuncturementioning
confidence: 99%